How to Increase Employee Performance at Bank Mandiri West Java Region Office - Yulius, Yopi (Dinasti International Journal of Economics, Finance & Accounting, 2022)
The purpose of this study was to determine work motivation, competence and employee performance at Bank Mandiri West Java Regional Office and the effect of work motivation and competence simultaneously or partially on employee performance at Bank Mandiri West Java Regional Office. The method used is descriptive and explanatory survey methods. The unit of analysis in this study is the employees at Bank Mandiri West Java Regional Office. The population was taken as many as 30 people who were taken by census, and the analytical methods used were frequency distribution and path analysis. The findings of this study are that work motivation and employee competence are quite good, and work motivation has an effect on performance and competence has an effect on performance, where employee performance will increase if employees of Bank Mandiri West Java Regional Office seek to increase motivation as the first priority, and job satisfaction as the second priority. , because the dominant motivation affects employee performance than job satisfaction.